Biofilms in shower hoses. (15th March 2018) - Proctor, Caitlin R.; Reimann, Mauro; Vriens, Bas; Hammes, Frederik
Abstract: Shower hoses offer an excellent bacterial growth environment in close proximity to a critical end-user exposure route within building drinking water plumbing. However, the health risks associated with and processes underlying the development of biofilms in shower hoses are poorly studied. In a global survey, biofilms from 78 shower hoses from 11 countries were characterized in terms of cell concentration (4.1 × 10 4 –5.8 × 10 8 cells/cm 2 ), metal accumulation (including iron, lead, and copper), and microbiome composition (including presence of potential opportunistic pathogens). In countries using disinfectant, biofilms had on average lower cell concentrations and diversity. Metal accumulation (up to 5 μg-Fe/cm 2, 75 ng-Pb/cm 2, and 460 ng-Cu/cm 2 ) seemed to be partially responsible for discoloration in biofilms, and likely originated from other pipes upstream in the building. While some genera that may contain potential opportunistic pathogens ( Legionella, detected in 21/78 shower hoses) were positively correlated with biofilm cell concentration, others ( Mycobacterium, Pseudomonas ) had surprisingly non-existent or negative correlations with biofilm cell concentrations. In a controlled study, 15 identical shower hoses were installed for the same time period in the same country, and both stagnant and flowing water samples were collected. Ecological theory of dispersal and selection helped to explain microbiome composition and diversity of different sample types. Shower hose age was related to metal accumulation but not biofilm cell concentration, while frequency of use appeared to influence biofilm cell concentration. This study shows that shower hose biofilms are clearly a critical element of building drinking water plumbing, and a potential target for building drinking water plumbing monitoring. Graphical abstract: Highlights: Biofilms from 93 shower hoses from 11 countries on 3 continents were characterized. When disinfectant was used, total cell concentration and diversity were lower. Opportunistic pathogens correlated positively and negatively with cell concentration. Engineering and consumer choices shaped shower hose biofilms.